ANALYSIS OF HUMAN RESOURCES DEVELOPMENT PLANNING IN THE FIELD OF FINANCE IN BAPPEDA AND LITBANG DOGIYAI DISTRICT - Yoptan, Selfianus; Roreng, Petrus Peleng; Toding, Apriana (Entrepreneurship Undergraduate Program at Amkop Business School, 2025)
This study analyzes the planning of human resource development in finance at Bappeda and Litbang of Dogiyai Regency. Using a qualitative descriptive approach, data were collected through surveys, observations, interviews, and documentation. The findings reveal that human resource development planning in finance is an integral and systematic process, ensuring employees are equipped with the necessary skills to manage regional finances effectively. Key programs, such as financial analysis training and regulatory workshops, have been implemented to enhance employee competencies. However, challenges such as limited budget allocation, lack of management support, and restricted access to training information hinder development efforts. Addressing these challenges requires comprehensive strategies, including increased budget allocation, management reinforcement, and improved access to training opportunities. This research underscores the importance of structured human resource development in achieving efficient financial management and supporting regional economic growth.